ROLE OF THE REGULATORY T CELLS IN PROGRESSION OF PROSTATE CANCER - S. V. Popov (SPb RAACI, 2019)
The existing data on regulatory T cells (Tregs) in prostate cancer suggest that these cells may penetrate the prostate gland malignant tissue, suppressing antitumor immune response, thus promoting aggressive clinical course and low survival of the cancer patients. Evaluation of T cell subpopulations from the tumor microenvironment has shown that the number of CD4+Tregs is associated with inferior clinical prognosis. In particular, each additional CD4+Treg cell has been shown to cause a statistically significant increase in prostate cancer mortality by 12%, regardless of other clinical factors. There are several possible explanations for the increased infiltration of prostate cancer tissue with regulatory T cells. Firstly, malignant cells or tumor-associated macrophages are capable of secreting chemokine CCL22, which has an affinity for the CCR4 receptor expressed on Treg cells. Secondly, cytokines secreted by prostate tumors, such as TGF-β, may regulate the FoxP3 expression, thus expanding the Treg population. TGF-β, in turn, is a multifunctional cytokine that promotes survival and proliferation of transformed cells, including prostate epithelium, as evidenced by increased amounts in the patients with metastatic disease.